2020
DOI: 10.20473/jn.v15i2.16930
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence and Postpartum Depression

Abstract: Introduction: Domestic violence occurs at all levels of society. Evidence shows that sexual, physical and psychological violence are predisposing factors of postpartum depression. This study was aimed to determine the relationship between domestic violence and postpartum depression.Methods: This research adopted quantitative method through observational with a cross-sectional study design by analyzing secondary data from SEHATI longitudinal surveillance. A total of 232 women was selected as sample  using a pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Previous research analyzing this method has shown its ability to strengthen psychological responses. 20 It was found that the suggestion group reported a 42% lower subjective pain intensity, effectively handled anxiety during the biopsy process, and experienced a 14% reduction in hospitalization time after surgery (19 hours). Additionally, they reported 11% less pain in the days following the operation, along with reductions in postoperative pain, blood pressure, and increased confidence in competition.…”
Section: Introductionmentioning
confidence: 96%
“…Previous research analyzing this method has shown its ability to strengthen psychological responses. 20 It was found that the suggestion group reported a 42% lower subjective pain intensity, effectively handled anxiety during the biopsy process, and experienced a 14% reduction in hospitalization time after surgery (19 hours). Additionally, they reported 11% less pain in the days following the operation, along with reductions in postoperative pain, blood pressure, and increased confidence in competition.…”
Section: Introductionmentioning
confidence: 96%